Correction to: A DM1-doped porous gold nanoshell system for NIR accelerated redox-responsive release and triple modal imaging guided photothermal synergistic chemotherapy - Pengcheng Xu; Ru Wang; Wenqian Yang; Yanyan Liu; Dongsheng He; Zixuan Ye; Daquan Chen; Yuan Ding; Jiasheng Tu; Yan Shen (Journal of Nanobiotechnology, 2021)
An amendment to this paper has been published and can be accessed via the original article.